Application of Consent to Perform Medical Actions (Informed Consent) Doctors in Medical Services at Hospitals in Palu City - Anna Veronica Pont; Enggar Enggar (Poltekita : Jurnal Ilmu Kesehatan, 2023)
This research aims to know how about the implementation Informed Consent is executed on medic al services in the hospitals in the city of Palu appropriated to rule of Minister of Health Number 290/MENKES/PER/III/2008, and to know the barriers which are faced in the implementation Informed Consent on medical services in teh hospitals in the city of Palu. This research is an empirical legal research or non doctrinal research. The techniques of collection of legal materials is done through observations, interviews, and distributing questionnaires to the respondents by purposive sampling method. All data collected were described and analyzed descriptively, by looking the data percentage collected, and showed in teh form of frequency distribution tabel, and then classified the muchly percentage from each respondents, ethical feasibility from the Research Ethics Commission of the Poltekkes of the Ministry of Health Palu Number 005.1/KEPK-KPK/1/2023 . The result showed that the implementation of Informed Consent on medical services in the hospitas in the city of Palu is appropriated to the Rule of minister of health Number 290/MENKES/PER/III/2008 about the lacks of its implementation, that come from medical nurses as well as from patients. Suggestion that given is to make team for applying informed consent in the hospital that consist of specialis surgery, specialis anaesthesi, psykology, and a standart operational.